A near repeat examination of economic crimes - Powell, Zachary A. (Crime & delinquency, 2019)
Criminological inquiry has recently showcased increased attention toward the near repeat phenomenon, which suggests that following an initial criminal event, there is an increased risk for the occurrence of the same type of event spatially and temporally proximate to the initiating event. The majority of previous research tends focuses on the patterns related to violent and conventional property crimes but neglects to examine other economic-related crimes. Given the significant costs associated with this crime type, unpacking hidden patterns may be useful in identifying high-risk areas and deploying appropriate countermeasures. The current study builds on previous examinations of the near repeat phenomenon through the exploration of specific economic crimes (counterfeiting, credit card/ATM fraud, false pretense/swindling) using 6 years of crime data from the Fort Worth (Texas) Police Department. Although near repeat patterns were discovered across multiple analyses, the greatest risk across all analyses was for repeat victimization at the same location. A discussion of policy implications, limitations, and areas for future research are also provided.